2020
DOI: 10.3389/fped.2020.00172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Heterogeneity in Six Tunisian Families With Horizontal Gaze Palsy With Progressive Scoliosis: A Retrospective Study of 13 Cases

Abstract: Background: Horizontal Gaze Palsy with Progressive Scoliosis (HGPPS) is a rare autosomal recessive congenital disorder characterized by the absence of conjugate horizontal eye movements, and progressive debilitating scoliosis during childhood and adolescence. HGPPS is associated with mutations of the ROBO3 gene. In this study, the objective is to identify pathogenic variants in a cohort of Tunisian patients with HGPPS and to further define ROBO3 genotype-phenotype correlations. Methods: Thirteen Tunisian patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…When better reported, progressive scoliosis is in the thoracic or thoracolumbar area [18] and presents with varying levels of severity that justify physical therapy, braces, and, more often, spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When better reported, progressive scoliosis is in the thoracic or thoracolumbar area [18] and presents with varying levels of severity that justify physical therapy, braces, and, more often, spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…From the first published case of HGPPS in 1975 to the recent, extrapyramidal signs have been occasionally reported along with cardinal manifestations of the disease, as facial myokymia was one of the significant signs of the very first reported patient with HGPPS [6] and some other extrapyramidal findings such as torticollis and head titubation, mentioned in many of afterward case reports; Nevertheless, not only the pathophysiology of these signs has not been fully explained, but also in some level ignored to be considered as a part of the syndrome. Although some authors have been focusing on extrapyramidal findings in HGPPS by arranging them into different categories [5,7], but there is no further investigation to any of those.…”
Section: Discussionmentioning
confidence: 99%
“…30 cases had a sign of extrapyramidal involvement, consisting 32% of total reports. Torticollis was the most reported clinical finding corelate with extrapyramidal manifestation, observed in 43% of these cases [5,[8][9][10][11], followed by dystonic head tremor detected in 40% of cases [7,[12][13][14][15] and facial contraction developed in 20% of cases [7,15,16]. One patient showed the combination of facial spasm along with dystonic head tremor [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that four distinct homozygous mutations in the ROBO3 gene were responsible. Two of those mutations novel homozygous, causing effective damage to the protein by in-silico analysis [65]. Another disease with genetic heterogeneity is cerebral palsy (CP) a common, clinically heterogeneous set of disorders that affects the movement and posture of an individual.…”
Section: Diseases With Clinical and Genetic Heterogeneitymentioning
confidence: 99%